Assessment of P-wave dispersion in children with atrial septal aneurysm. (25th September 2013) - Arslan, Derya; Cimen, Derya; Guvenc, Osman; Oran, Bulent; Yilmaz, Fatma Hilal
Abstract Background This was a prospective controlled study to determine the P-wave duration and P-wave dispersion in patients with atrial septal aneurysm. Methods A total of 41 children with atrial septal aneurysm, including 21 boys and 20 girls (mean age 11.85 ± 3.8 years), and 32 controls, including 17 boys and 15 girls (mean age 12.3 ± 2.9 years), were included. P-wave dispersion was calculated from the 12-lead electrocardiogram. Cardiac functions, morphology of the aneurysm, and left atrial diameter were measured using conventional echocardiography. The diagnosis of atrial septal aneurysm was made when the base of the aneurysms with an excursion ratio ≥25% was found on echocardiography. Results There was no significant difference between the patient and control groups in demographic, clinical findings, and M-mode echocardiographic parameters. The P-wave dispersion in patients with atrial septal aneurysm was significantly longer compared with the control group (64.4 ± 13.4 ms; p < 0.0001). Similarly, the the maximum duration of the P wave in the patient group was significantly longer compared with the control group (106.1 ± 13.3 ms; p < 0.001). The P-wave duration and dispersion were not correlated with age, gender, systolic and diastolic blood pressure, or m-mode echocardiographic parameters. Conclusions This study shows that P-wave dispersion is delayed in atrial septal aneurysm patients. Prolonged P-wave dispersion was determined to indicate electrical disturbance, and therefore it has an increased electrocardiographic risk of atrial arrhythmia in children with atrial septal aneurysm.